Retraction notice to "Natural resources environmental quality and economic development: Fresh analysis" [Resources Policy 79 (2022) 102948]. (December 2022) - Meng, Dong; Iqbal, Nadeem; Zhao, Shaodong
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editors-in-Chief. The main part of the paper focuses on Europe, but Sections 4.3 and 4.4 discuss the provinces of China. Apologies are offered to the readers for failing to detect it during the peer-review process.